Intercultural learning as a key qualification in the age of globalisation in the context of German lessons in Georgia - Loladze, Nino (Glottodidactica, 2009)
In the age of globalisation, foreign language classes play an especially important part. Considering the inextricable link between the study of language and of culture, in foreign language classes not only aim language structure, but also aim language culture must be taught. The need for intercultural learning must be recognised also in the German as a foreign language classes in Georgia and this approach must show up in the formation of teachers as well as in the new books on German as a foreign language in Georgia.